Condensate dynamics at the synapse: Phase separation tunes presynaptic function. - Janine Lützkendorf; Stephan J Sigrist (PLoS Biology)
A new study in PLOS Biology shows that Liprin-α and RIM form condensates which not only scaffold presynaptic protein architectures but also fine-tune vesicle priming and release dynamics.